The Development of Integrative Entrepreneurship Education based on Local Wisdom through "Jagong Maton" - Fantika Febry Puspitasari; Sigit Priatmoko (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2021)
The high contribution of education graduates to the number of unemployed is suspected to be due to the lack of mastery of special skills, especially in entrepreneurship. While the development of entrepreneurship skills so far has only focused on vocational education such as vocational schools. Islamic boarding schools have substantial social capital in creating social change through entrepreneurship education from a historical perspective. This factor became the basis for the Al Amin Sumberpucung People's Islamic Boarding School to develop an integrative entrepreneurship education based on local wisdom through the Jagong Maton method. This study aims to determine the concept, implementation, and results of the development of entrepreneurship education through Jagong Maton at Pesantren Rakyat Al Amin Sumberpucung. This research is a field study that uses a descriptive method with a qualitative approach. The study results stated that: 1) The Jagong Maton method produced two bases of local wisdom entrepreneurs, namely the type of entrepreneur with local wisdom and the type of general entrepreneur, which was developed based on the local community's need. 2) Implementation of entrepreneurship education with a humanist-socio-cultural approach, meaning according to the interests of students' talents and the socio-cultural conditions of the surrounding community. Types of business include agriculture, animal husbandry, herbal medicine production, orchid cultivation, refilling mineral water, Javanese musical instruments, and puppets. 3) Entrepreneurial education results include the ability to meet personal needs, the formation of an integrative entrepreneurial spirit, and the formation of entrepreneurial abilities in students.